Characteristics of Soto, an ethnic food that reflects Indonesian diversity: Based on ingredients - Laras Cempaka; Afifah Amalia Rizki; Nurul Asiah; Wahyudi David; Kurnia Ramadhan; Arnia Sari Mukaromah; Hegar Pramastya; Fadly Husain; Nurul Huda (Hasanuddin University Food Science and Technology Study Program, 2023)
Indonesia is highly diverse in culture, ethnicity, religion, and natural resources. The diversity is also obvious in its cuisine. Soto is an example of an iconic Indonesian dish found in many parts of the country. Despite sharing a similar name, the recipes vary according to their place of origin. Until now, how many variants of Soto are in Indonesia is not exactly known. This review aimed to discuss the characteristics of Soto based on ingredients. Soto is a soup composed of spices-flavored broth and various solid ingredients, such as vegetables and protein-and carbohydrate-rich foods. Every region in Indonesia has a different recipe of Soto; some use non-turmeric soup or coconut milk soup. The carbohydrate ingredients are mainly soun (cellophane noodle) and potato. The protein ingredients are mainly composed of chicken, egg, and beef. Vegetables consist of bean sprouts, tomatoes, and cabbage. Fried garlic, shallot, spring onion, and crackers are added as a garnish. The diversity of the ingredient makes the distinction among Soto: diversity of locality and diversity of ingredients. Approximately 46 types of Soto are reviewed in this article. Most of the Soto recipes use chicken, bean sprouts, soun, boiled egg, garlic, white pepper, red onion, ginger, and bay leaf as the main ingredients. Soto becomes an identity of its geographical origins and has distinction based on the main recipes.